Protective effects of relaxin in ischemia/reperfusion-induced intestinal injury due to splanchnic artery occlusion - Masini, Emanuela (Nature Publishing Group, 2006)
1. Splanchnic artery occlusion (SAO) followed by reperfusion causes endothelial injury and inflammation which contribute to the pathophysiology of shock. We investigated the effects of relaxin (RLX), known to afford protection against the deleterious effects of cardiac ischemia/reperfusion, given to rats subjected to splanchnic artery occlusion and reperfusion (SAO/R)-induced splanchnic injury. 2. RLX (30 ng kg(−1), 15 min. before reperfusion) significantly reduced the drop of blood pressure and high mortality rate caused by SAO/R. RLX also reduced histopathological changes, leukocyte infiltration (myeloperoxidase) and expression of endothelial cell adhesion molecules in the ileum. RLX counteracted free radical-mediated tissue injury, as judged by significant decrease in the tissue levels of peroxidation and nitration products (malondialdehyde, nitrotyrosine), DNA damage markers (8-hydroxy-2′-deoxyguanosine, poly-ADP-ribosylated DNA) and consumption of tissue antioxidant enzymes (superoxide dismutase). As a result, RLX led to a reduction of ileal cell apoptosis (caspase 3, terminal deoxynucleotidyltransferase-mediated UTP end labeling). The effects of RLX appear specific, as inactivated RLX substituted for the bioactive hormone had no effects. 3. In conclusion, these results show that RLX exerts a clear-cut protective effect in SAO/R-induced splanchnic injury, likely due to endothelial protection, decreased leukocyte recruitment and hindrance of free radical-mediated tissue injury leading to cell death, lethal complications and high mortality rate. Thus, RLX could be used therapeutically in intestinal ischemia.